Effect of Service Marketing Mix, Electronic Service Quality, Technology Acceptance toward Satisfaction in Ordering Food Delivery through the Application of Consumer in Lampang Province - Punyayuen, Jurarat; Wingwon, Boonthawan (RMUTL Journal of Business Administration and Liberal Arts, 2022)
The purpose of this research was to study the importance of the service marketing mix, e-service quality, technology acceptance, and satisfaction, and to study the effect of the service marketing mix, e-service quality, and technology acceptance toward satisfaction ordering food delivery through the consumer application in Muaeng Lampang District, Lampang Province. It is quantitative research. The sampling group was 384 consumers who have used the food delivery service through the application. The tool was a questionnaire. Data were used descriptive statistics to find percentages, averages, and standard deviation, inferential statistics were used multiple regression to analyze with Enter selection technique. The outcomes of the research study revealed that all factors were at a high level, of e-service quality, followed by technology acceptance and service marketing mix in equal proportions and the last satisfaction. The outcomes of multiple regression analysis were that the e-service quality had direct effect toward satisfaction, and followed by technology acceptance had direct effect toward satisfaction, and service marketing mix had direct effect toward satisfaction, by all factors were significant at 0.05. Thus, this research has resulted in online business operators to develop and improve their services for planning and formulate marketing strategies to consumer needs and drive the online business to be able to compete continuously.